Systemic Amelioration via Curcumin in Rats following Splenectomy: Lipid Profile, Endothelial and Oxidative Damage. Issue 6 (3rd July 2021) - Altinel, Yuksel; Kose, Emin; Karacaglar, Aysel; Demirgan, Serdar; Sozer, Volkan; Ozkaya, Guven; Gulcicek, Osman Bilgin; Simsek, Gonul; Uzun, Hafize
Abstract: Background: We investigated the postsurgical effects of splenectomy with additional curcumin therapy, as an antioxidant, anti-inflammatory substance among the lipid profile and histopathological changes. Materials and Methods: 32 rats were randomly divided into four groups: control group (L): laparotomy, sham group: splenectomy (S), splenectomy group treated with curcumin (SC) and splenectomy group treated with corn oil (SCO) for 28 days. The primary outcomes; total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), oxidized LDL (ox-LDL) very-low-density lipoprotein (VLDL) and lectin-type oxidized LDL receptor 1 (LOX-1), secondary outcomes: nuclear factor kappa B (NF-кB), malondialdehyde (MDA), glutathione peroxidase (GPx), superoxide dismutase (SOD) were measured. Histopathological changes were examined in vascular, intestinal and lung tissues. The analysis was performed by ANOVA. Results: TG, LDL, ox-LDL, and LOX-1 elevated in S group while reduced by curcumin compared with L group (p < 0.05). Serum and tissue levels of NF-кB and MDA were higher in S group and lower in SC group than L group (p < 0.05). Serum and intestinal levels of SOD and GPx increased in L group while reduced by curcumin (p < 0.05). Total histopathological scores of intestinal tissues were higher in S and SCO groups compared to L and SC groups (p < 0.05). No major changes in vascular and lung tissues were observed except the lymphoid follicles which was higher in S and SCO groups compared to L and SC groups (p < 0.05). Conclusions: Curcumin partially improved the lipid profile dysfunction by modulating NF-кB, MDA, SOD, and GPx in splenectomized rats while less likely improving any vascular and alveolar regeneration.